An 11-year-old girl with genital ambiguity: a case of non-classical congenital adrenal hyperplasia (BIRDEM Medical Journal, 2020)
Congenital adrenal hyperplasia (CAH) describes a group of autosomal disorders where there is impairment of cortisol biosynthesis. Here is a case of 11-year-old girl who presented with enlargement of external genitalia, excessive growth of hair in pubis, axilla, face and lower limbs along with growth spurt, excessive sweating and deepening of voice for 4 years. On examination she had normal body habitus, hirsutism (modified Ferriman- Gallwey Score-8), acanthosis nigricans in neck and axillary region, Tanner staging revealed stage-II breast development and stage IV female pattern pubic hair. Genitalia examination showed clitoromegaly with normal labia majora, minora and urethral position. Chromosomal analysis showed a normal female 46XX karyotype with normal uterus and bilateral ovaries on ultrasonography. Serum testosterone was elevated and 17- hydroxyprogesterone (17 OHP) was mildly elevated, raising the suspicion of non-classical congenital adrenal hyperplasia which was confirmed later by performing short Synacthen test. Patient and her parents were counseled regarding the diagnosis and clitoroplasty was done and prednisolone 5 mg daily at night in reverse circadian rhythm started. After 3 months of treatment, her hirsutism significantly reduced and menstruation had begun.Birdem Med J 2020; 10(3): 204-206